Case Report: Extrapelvic Endometriosis in the Medial Thigh - Pascoal, Erica; Rogers, Stacey; Leonardi, Mathew; Leyland, Nicholas (Frontiers in Reproductive Health, 2021)
Extrapelvic endometriosis, although rare, can present in the musculoskeletal system of reproductive-age women and cause significant pain and morbidity. The pathophysiology of this disease is not well understood. In this study, we described the case of a 39-year-old women with an inner-thigh mass causing catamenial pain. Core-biopsy of the mass confirmed endometriosis and she was referred to minimally-invasive gynecology for management. Surgical excision was performed by a multidisciplinary team and she remains pain-free postoperatively on hormonal therapy. Unique to this case, the patient had a history of pelvic fracture. Through this case report, we discuss possible pathophysiologic mechanisms of extrapelvic musculoskeletal endometriosis including the stem/progenitor cell theory and the role that musculoskeletal trauma may have in the development of this condition. Gynecologists play an important role in the recognition, diagnosis, and management of musculoskeletal endometriosis.